Tunable Q-switched erbium doped fiber laser with graphene oxide paper based saturable absorber - Ahmed, M.H.M.; Banabila, A.M.; Latiff, A.A.; Irawati, Ninik; Ali, N.M.; Harun, Sulaiman Wadi (INOE, 2016)
We demonstrate a tunable wavelength Q-switched erbium doped fiber laser (EDFL) using a graphene oxide (GO) saturable absorber (SA). The GO solution was prepared using the simplified Hummer’s method, which is then thinly spread into a petri-disk to make a paper-like material. The GO paper is sandwiched between two FC/PC fiber connectors and incorporated into a ring EDFL’s cavity for Q-switching operation. The wavelength tunable operation of the Q-switched laser was obtained with a band-pass filter. The stable Q-switched pulse with a tunable range from 1536 nm to 1563 nm was achieved, covering a wavelength range over ~28 nm. The Q-switched EDFL produced maximum pulse energy of 151 nJ at pump power of 80 mW.